1987
DOI: 10.1111/j.1365-3083.1987.tb02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Phenotype and Function in Patients with the Acquired Immunodeficiency Syndrome (AIDS) and AIDS‐Related Disorders

Abstract: The CD4 molecule, which is known to play an important role in the susceptibility of T lymphocytes to infection by the human immunodeficiency virus (HIV), is also expressed in small amounts on the surface of monocytes. Since monocytes can also be infected by the virus, we investigated peripheral blood monocytes of patients with the acquired immunodeficiency syndrome (AIDS), AIDS-related complex (ARC), and HIV seropositive and seronegative haemophiliacs without symptoms for the expression of the CD4 molecule and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Previous studies have not identified distinct abnormalities in monocyte cell surface antigens in HIV-infected individuals (53). However, these earlier studies used a less extensive battery of mAb reagents and did not attempt to relate changes in monocyte antibacterial activity to changes in cell surface phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have not identified distinct abnormalities in monocyte cell surface antigens in HIV-infected individuals (53). However, these earlier studies used a less extensive battery of mAb reagents and did not attempt to relate changes in monocyte antibacterial activity to changes in cell surface phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…Some of the differences of monocyte phenotype between HIV" and HIV* subjects, we observed, are novel (e,g, decreased proportional CD14and CDI lb expression), others were controversial (eg, up-regulation of CDlla and HLA-DR) [7][8][9][10], whereas our data on increased proportional FC7RIII expression confirm earlier reports [21], It was also previously shown that the FC7RI density was increased on monocytes from HIV* subjects [11]. We show here in addition that the proportion of Fc7RI*'"*'^'* monocytes is actually decreased in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of monocytes (37)(38)(39)(40) and alveolar M (39) from HIVϩ individuals have reported normal levels of CD11b, and CD11c has been found to be both decreased (40) and increased (37, 41) on monocytes from AIDS patients. Monocytes from asymptomatic HIVϩ individuals have been found to have increased levels of CD11a, CD11b, and CD11c (41,42).…”
Section: Discussionmentioning
confidence: 99%